Analysis of Environmental Literacy Skill of Biology Teacher Candidates in Human and Environmental Courses - Nike Anggraini; Khoiron Nazip; Puteri Kusuma Wardhani; Dian Sri Andriani (Universitas Muhammadiyah Sidoarjo, 2021)
This study examines the environmental literacy abilities of prospective Biology teacher students in the Biology Education Study Program, FKIP Sriwijaya University. The research subjects are Palembang and Indralaya class students who are teaching Human and Environmental Sciences Courses for the 2019/2020 academic year in Semester II. The skills measured in this study are Environmental Knowledge, Environmental Competence and Attitudes towards the environment formulated by the OECD and NAEE. The method used in this research is descriptive quantitative, with research subjects totaling 75 students. The technique of collecting data is through interviews, and surveys using an instrument sheet consisting of 20 multiple choice questions, 20 essays and 20 attitude scales. The data analysis technique used the SPSS 18 program. The test instrument used was modified from the Middle Schools Environment Survey/Instrument (MSELS/I) test questions and adapted to the physical conditions and environmental problems in the city of Palembang. The results showed that the prospective Biology teacher students were in the medium category for the Environmental Knowledge and Competence aspect, and got the high category for Environmental Attitudes.